Changes in adenomyosis following elagolix vs leuprolide treatment in a patient with pelvic pain and infertility: A case report - Mariam Barseghyan; J. Graham Theisen; Clara Wang; Larisa Gavrilova-Jordan (Elsevier, 2023)
Adenomyosis is a uterine form of endometriosis that poses unique challenges in the management of infertility. Severe pelvic pain and menorrhagia associated with these conditions are commonly managed with intramuscular injections of a gonadotropin-releasing hormone agonist (leuprolide acetate). Since receiving approval by the US Food and Drug Administration in 2018, a novel oral gonadotropin-releasing hormone antagonist, elagolix, has also been increasingly used to manage endometriosis-associated pain. However, the efficacy of elagolix in the treatment of adenomyosis and infertility remains uncertain. In this clinical case of an infertile patient with endometriosis and diminished ovarian reserve, treatment with elagolix effectively controlled her severe endometriosis-related pelvic pain but, surprisingly, failed to prevent concurrent progression of adenomyosis. Subsequently, elagolix was changed to treatment with leuprolide acetate, which led to improvement of adenomyosis in preparation for an embryo transfer during an in vitro fertilization cycle. Women's health providers should be aware that elagolix may not as effectively suppress adenomyosis as leuprolide acetate, particularly in infertility patients undergoing treatment with assisted reproductive technologies.